23.4 PET-BASED PRECISION NEUROIMAGING OF THE ALPHA7 NICOTINIC ACETYLCHOLINE RECEPTOR IN PATIENTS WITH RECENT ONSET OF PSYCHOSIS. (9th April 2019) - Coughlin, Jennifer; Du, Yong; Crawford, Jeffrey; Rubin, Leah; Azad, Babak Behnam; Lesniak, Wojciech Lesniak; Horti, Andrew; Schretlen, David; Sawa, Akira; Pomper, Martin
Abstract: Background: Low availability of the α7 nicotinic acetylcholine receptor (α7-nAChR) in the hippocampus of patients with schizophrenia has been suggested from study of postmortem tissue, and therapies that increase signaling through the α7-nAChR may ameliorate signs and symptoms of psychosis, including associated cognitive deficits. Here we used [18F]ASEM with positron emission tomography (PET) to test for hypothesized low in vivo availability of the hippocampal α7-nAChR in individuals with recent onset psychosis compared to healthy controls. Building on the recent development of α7-nAChR-targeted medications and in line with precision health initiatives that aim to customize therapeutic strategies to patient subgroups, we also tested whether individuals with non-affective psychosis (NP) have lower [18F]ASEM binding compared to individuals with affective psychotic disorder (AP). Methods: This prospective study was approved by a Johns Hopkins Institutional Review Board. Each non-smoker participant provided written informed consent. Individuals with recent-onset (within five-years) psychosis were included if they had: 1) schizophrenia or schizoaffective disorder (grouped NP) or 2) bipolar I disorder (referred to as AP). Limited medication use (lithium or antipsychotic monotherapy) was allowed. Eleven patients and five new healthy controls completed [18F]ASEM PET, and we pooled their data with those of all ten healthy individuals < 50-years-old from our published study of the α7-nAChR in healthy aging. [18F]ASEM kinetics were modeled using Logan graphical analysis with a metabolite-corrected arterial input function from 90 min dynamic data. Hippocampal total distribution volume (VT) values were derived from images after partial volume correction (PVC). Group differences in VT were tested using analysis of variance and using analyses of covariance to control for potential confounding effects of age, sex, race, or body mass index (BMI). Results: Among individuals with recent-onset psychosis, five had NP [schizophrenia (N=3), schizoaffective disorder (N=2)] and six had AP. There were significant group differences [using three groups (Controls, AP, NP) or two groups (Controls, AP+NP)] on hippocampal VT (Ps ≤ 0.001), even after adjusting for age (each P = 0.001). Individuals with recent onset psychosis (AP+NP) had lower VT (15.97 ± 2.50) than healthy controls (19.55 ± 2.49, P = 0.001), though VT in the AP group alone (17.57 ± 2.24) did not differ from healthy controls. VT was lower in individuals with NP (14.05 ± 0.89) compared to healthy controls (P < 0.001) or compared to those with AP (P = 0.04) and remained lower in those with NP compared to healthy controls after adjusting for each covariate separately (Ps ≤ 0.002). Controlling for BMI or race did not change the lower VT in individuals with NP compared to AP (Ps = 0.01), but significance was lost after adjusting for age. Among patients (AP+NP), higher VT was associated with better processing speed and verbal memory after adjusting for age. VT estimates from images without PVC did not change these results and produced parametric images that support group differences outside hippocampus. Conclusions: These results suggest that low availability of the α7-nAChR may be linked to recent onset of psychosis, particularly recent onset of NP. Further study is needed to assess its clinical relationship to neuropsychiatric symptoms.